2018
DOI: 10.1016/j.bpj.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nucleocytoplasmic Transport due to Competition for Elastic Binding Sites

Abstract: Nuclear pore complexes (NPCs) control all traffic into and out of the cell nucleus. NPCs are molecular machines that simultaneously achieve high selectivity and high transport rates. The biophysical details of how cargoes rapidly traverse the pore remain unclear but are known to be mediated by interactions between cargo-binding chaperone proteins and natively unstructured nucleoporin proteins containing many phenylalanine-glycine repeats (FG nups) that line the pore's central channel. Here, we propose a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…Motion of multiple particles. In [3], we proposed a model for enhanced transport through the nuclear pore that relied on competition between two distinct species of particles for binding to a population of elastic tethers. Enhanced nuclear transport in that case depended on a set of biochemically motivated boundary conditions as well as the interaction between two distinct species of moving particles.…”
Section: Diffusion Mediated By Linearly-elastic Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion of multiple particles. In [3], we proposed a model for enhanced transport through the nuclear pore that relied on competition between two distinct species of particles for binding to a population of elastic tethers. Enhanced nuclear transport in that case depended on a set of biochemically motivated boundary conditions as well as the interaction between two distinct species of moving particles.…”
Section: Diffusion Mediated By Linearly-elastic Bindingmentioning
confidence: 99%
“…This situation is biologically relevant. It occurs in the nuclear pore complex in the interaction between karyopherin chaperones and elastic FG nucleoporins [3,8,9,13,15], and in a similar manner in the ciliary pore complex [6,12,17]. It is also relevant to the diffusion of signaling molecules near membranebound cognate receptors, where elasticity can come from the mechanical properties of the receptor or from the membrane itself.…”
mentioning
confidence: 99%
“…Binding does not always enhance flux across a barrier. Mechanisms of selective transport include transport by mobile carriers and particle motion directly from one binding site to the next [18][19][20][21][22][23]. In general, selectivity requires that particles move while bound.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic polymers allow a bound particle to move and may additionally drive motion due to elastic kicks when extended tethers bind ( Fig. 1B) (13,19,20). When applied to transport factors binding to disordered FG Nups within the NPC, a theory based on tethered diffusion agrees with experimental measurements of selective transport of NTF2 (4,13,21,22) suggesting that this mechanism may contribute to selective transport through the nuclear pore complex.…”
Section: Introductionmentioning
confidence: 62%
“…While previous work has shown that bound diffusion can lead to selective filtration (16)(17)(18), the molecular mechanisms that contribute to bound mobility and their relative importance remain poorly understood (13,19). We focus on determining whether binding to flexible tethers can lead to appreciable bound motion.…”
Section: Resultsmentioning
confidence: 99%